Adaptive Reliable Multi-Path Provisioning in WDM Mesh Networks - Sheng Huang; Mukherjee, B. (IEEE International Conference on Communications (2003), 2008)
We investigate the problem of adaptive reliable multipath provisioning in next-generation backbone mesh networks employing optical wavelength-division multiplexing (WDM) and channelization techniques such as SONET/SDH, and supporting virtual concatenation (VCAT). With VCAT, a connection request can be split, diversely routed, and inversely multiplexed on to multiple paths, a feature that has many advantages over conventional single-path provisioning, such as improved reliability, load balancing, etc. However, these diversely routed traffic components are subject to the differential delay constraints (DDC), which could be limited by the destination node's delay-compensation capability, network operations, administration, maintenance, and provisioning (OAM&P), or connection quality-of-service (QoS). We introduce a new notation M : N (m) for multipath provisioning where a service path for a connection is set up with M primary paths and N backup paths, where each path may have a fraction of the bandwidth of the connection, and (m) in this notation denotes "multipath'. We present the flexibility and benefits of multipath provisioning and develop an analytical model to analyze the connection availability under M : N (m) provisioning schemes. We propose two types of bandwidth migration methods, which can be implemented by link- capacity adjustment scheme (LCAS) protocol of next-generation SONET/SDH, to optimize resource usage. We develop two adaptive heuristic algorithms to provision a connection subject to DDC while satisfying its service-level agreement (SLA). We show that, for end-to-end connection-availability-guaranteed service, multi- path provisioning can achieve better network performance than traditional single-path provisioning. With bandwidth migration, we can further improve the performance.